Decision Support System Selection of The Best Citilink Agent Call Center Using the Fuzzy Ahp Method (analytical Hierarchy Process) (case Study: Pt. Infomedia Surabaya Call Center Citilink) - M Mahaputra Putra; Syariful Alim; Dhanu Budi Pangestu (Fakultas Teknik Universitas Bhayangkara, 2021)
For the selection of employees, there are usually many factors in fulfilling the assessment in order to get a maximum target. Especially in the field of call centers, it is required to have qualified skills which can solve problems complained of by customers. So that as a call center who receives incoming calls or can be called inbound calls, it must be the key to solving problems and be able to convey good suggestions. However, to get the value of the agent so that its performance is good, there are parameters that must be achieved, namely acd call, acd time, aux time, available time, staffed time and agent skill. best. By doing this, the monitoring system is very easy and more efficient to find out which agents are underperforming or agents who have reached the performance target. For this reason, an application with a case study was created in order to achieve the maximum target. This application will greatly help the team, namely Teamleader, Taber, Spv, Manager as they play an important role in evaluating agents in their performance.